2011
DOI: 10.4161/psb.6.4.14839
|View full text |Cite
|
Sign up to set email alerts
|

Indirect effects of tending ants on holm oak volatiles and acorn quality

Abstract: T he indirect effect of ants on plants through their mutualism with honeydew-producing insects has been extensively investigated. Honeydewproducing insects that are tended by ants impose a cost on plant fitness and health by reducing seed production and/ or plant growth. This cost is associated with sap intake and virus transmissions but may be overcompesated by tending ants if they deter or prey on hebivorous insects. The balance between cost and benefits depends on the tending ant species. In this study we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
2
0
1
Order By: Relevance
“…However, ecological interactions between two species can often be indirectly mediated by a third species [3] , [8] – [11] . This type of interaction is described in the literature mainly regarding plant defenses against herbivores (performed by ants) [12] [16] , the attraction of parasitoids by volatile substances produced by plants under attack by herbivores [17] , [18] , and interactions in which the presence of endophytic fungi, pathogens, or mycorrhizae defends the plants by producing secondary metabolites that have different effects on the performance of herbivores [19] [23] . These interactions are spatially and temporally dynamic and can be difficult to distinguish [24] .…”
Section: Introductionmentioning
confidence: 99%
“…However, ecological interactions between two species can often be indirectly mediated by a third species [3] , [8] – [11] . This type of interaction is described in the literature mainly regarding plant defenses against herbivores (performed by ants) [12] [16] , the attraction of parasitoids by volatile substances produced by plants under attack by herbivores [17] , [18] , and interactions in which the presence of endophytic fungi, pathogens, or mycorrhizae defends the plants by producing secondary metabolites that have different effects on the performance of herbivores [19] [23] . These interactions are spatially and temporally dynamic and can be difficult to distinguish [24] .…”
Section: Introductionmentioning
confidence: 99%
“…Por otra parte, el ICP de Dickson indica la potencialidad de una plántula para sobrevivir y crecer en ciertas condiciones; así, plántulas con mayor calidad tienen índices de calidad más altos (Paris et al 2011). Los bajos valores del ICP obtenidos en este trabajo son comparables con aquellos reportados para plántulas de Quercus silex (0.072 y 0.015), y que se atribuyeron a la baja calidad de los propágulos de donde se obtuvieron dichas plántulas (Paris et al 2011). Lo anterior sugiere que bajo nuestras condiciones de estudio y el tiempo en el cual se hizo la evaluación (120 días), las plantas aún se encontraban en periodo de crecimiento activo, por lo que se sugiere llevar a cabo estudios a largo plazo.…”
Section: Discussionunclassified
“…Plant volatiles are also probably involved in the recognition of weakened, damaged hosts (Allison et al 2004;Hanks et al 2012). Moderate EAG responses were elicited in P. myardi by three compounds associated with emissions from wounded leaves of Quercus species: the known ubiquitous GLV (E)-2-hexenal, two acyclic monoterpenes, β-myrcene and (E)-β-ocimene (Paris et al 2011;Pearse et al 2013), and 3-methyl-butanol (found in microbially colonized cork from Q. suber (Rocha et al 1996)). …”
Section: Discussionmentioning
confidence: 99%